Effect of Flash Light Sintering on Silver Nanowire Electrode Networks - Yang, Dae-Jin (Materials (Basel), 2020)
We investigated the flash light sintering process to effectively reduce electrical resistance in silver nanowire networks. The optimum condition of the flash light sintering process reduces the electrical resistance by ~20%, while the effect of the conventional thermal annealing processes is rather limited for silver nanowire networks. After flash light sintering, the morphology of the junction between the silver nanowires changes to a mixed-phase structure of the two individual nanowires. This facile and fast process for silver nanowire welding could be highly advantageous to the mass production of silver nanowire networks.